2017
DOI: 10.1136/svn-2016-000063
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of cost-effectiveness of intravenous recombinant tissue plasminogen activator for treating acute ischaemic stroke

Abstract: BackgroundIntravenous recombinant tissue plasminogen activator (IV rtPA) is recommended treatment for patients with acute ischaemic stroke, but the cost-effectiveness of IV rtPA within different time windows after the onset of acute ischaemic stroke is not well reviewed.AimsTo conduct a literature review of the cost-effectiveness studies about IV rtPA by treatment times.Summary of reviewA literature search was conducted using MEDLINE, EMBASE, CINAHL and Cochrane Library, with the keywords acute ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…For example, the provision of thrombolysis and EVT appears to be more cost-effective when considering downstream costs in the longer term. 2628…”
Section: Discussionmentioning
confidence: 99%
“…For example, the provision of thrombolysis and EVT appears to be more cost-effective when considering downstream costs in the longer term. 2628…”
Section: Discussionmentioning
confidence: 99%
“…Although lack of resources is often perceived as a barrier to Open access system change, 53 we demonstrated that much can be accomplished through reorganisation of existing services. We did not conduct a cost analysis, but other studies have demonstrated the cost-effectiveness of thrombolytic therapy, 54 and it has been estimated that optimising comprehensive stroke care in Canada could avoid costs of $682 million annually. 55…”
Section: Discussionmentioning
confidence: 99%
“…These two advanced therapies have been shown to lead to reduced mortality and improved functional outcomes of ischemic stroke patients [32,33], which can shorten the length of hospital stay [34,35]. Despite higher costs in the acute phase, thrombolysis and endovascular thrombectomy have been established to be cost-effective [36,37]. Intravenous thrombolysis and endovascular therapies are, however, unsuitable for many stroke patients; a recent survey showed that in Finland, 12.6% of stroke patients received intravenous and only 3.6% endovascular treatment [38].…”
Section: Discussionmentioning
confidence: 99%